2021
DOI: 10.3390/app11125579
|View full text |Cite
|
Sign up to set email alerts
|

Role of Irisin in Endocrine and Metabolic Disorders—Possible New Therapeutic Agent?

Abstract: Irisin is a novel hormone that provides a possible solution for the treatment of metabolic disorders. Discovered in 2012 by Boström et al., irisin very quickly became an interesting subject in medical research. Irisin has been found in cerebrospinal fluid, the cerebellum, thyroid, pineal gland, liver, pancreas, testis, spleen, adult stomach, and human fetuses. Regarding the actions of irisin, both in animals and humans, the results are contradictory but interesting. Its capability to influence adipose tissue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Such findings question all previous data obtained with these kits, and until these methodological aspects are resolved, studies relying on these measures should be carefully scrutinized. In summary, this review and meta-analysis may have some evidentiary support for the positive long-term effects of exercise on blood irisin levels, but more importantly, it points to the important methodological issues related to the actual detection of irisin [90], which should be considered when conducting research in this area [85]. In summary, our results confirm the general notion that exercise increases irisin levels in obese and older people.…”
Section: Summary Of Main Results and Interpretationssupporting
confidence: 80%
See 1 more Smart Citation
“…Such findings question all previous data obtained with these kits, and until these methodological aspects are resolved, studies relying on these measures should be carefully scrutinized. In summary, this review and meta-analysis may have some evidentiary support for the positive long-term effects of exercise on blood irisin levels, but more importantly, it points to the important methodological issues related to the actual detection of irisin [90], which should be considered when conducting research in this area [85]. In summary, our results confirm the general notion that exercise increases irisin levels in obese and older people.…”
Section: Summary Of Main Results and Interpretationssupporting
confidence: 80%
“…More importantly, exercise including resistance training [44], aquaerobic training [50], endurance training [55], golf [61], low-intensity resistance training [66], high-intensity interval training [69], and treadmill walking [51] increased irisin blood levels in healthy older females and resistance training [82] in healthy older males, which may, in fact, protect against bone loss and muscle atrophy [6]. In this case, irisin might provide a therapeutic choice for treating diseases caused by inactivity (which often is the case for older adults), including osteoporosis and sarcopenia, or it may be used as a useful biomarker for the assessment of bone and muscle health as suggested by Leustean et al [85]. Especially, the older adult female population would benefit from this protective effect as they are prone to osteoporosis.…”
Section: Summary Of Main Results and Interpretationsmentioning
confidence: 99%
“…Numerous data have suggested the putative effect of increased irisin levels on reverting or retarding obesity and aging progression, based on renowned biomarkers, such as glycemia and total cholesterol levels (92). Previous studies have shown that irisin can act as a regulatory factor to control diabetes and obesity during aging (93).…”
Section: Irisin and Agingmentioning
confidence: 99%
“…Recently, irisin is thought to be a therapeutic hormone that can positively affect depressive behaviors through its effect on neuronal activities in the prefrontal cortex [84,85]. Moreover, some studies suggest that exercise-induced irisin ameliorates depressive symptoms by activating the PGC-1α-FNDC5/irisin pathway in the hippocampus [21,86].…”
Section: Irisinmentioning
confidence: 99%